Ethnochemistry In Chemistry Learning: Insights from Indonesian Local Wisdom - Junaidi, Eka; Sudatha, I Gde Wawan; Suartama, I Kadek; Santosa, Made Hery (FKIP Universitas Lampung, 2025)
This study aims to analyze the role of ethnochemistry as an innovative approach in chemistry education by examining its impact and development strategies based on local wisdom. Ethnochemistry combines cultural practices with chemical concepts to create meaningful and inclusive learning. This study focuses on the impact of ethnochemistry on chemistry learning and its development strategies to support inclusive and multicultural chemistry education. These findings are expected to enrich culturally relevant chemistry education and support the preservation of cultural heritage. This study employed the Systematic Literature Review (SLR) method, adhering to the PRISMA protocol to ensure transparency and repeatability. The initial search was conducted in Scopus, Google Scholar, Semantic Scholar, and Crossref, using the keyword